Nasab Bayi Tabung dari Ibu Pengganti (Studi Komparasi Antara Hukum Islam dan Hukum Positif): Lineage of Test-tube Baby from Substitute Mother (Comparative Study Between Islamic Law and Positive Law) - Muh. Fadil Majid; Ahmad Syaripudin; Aswin, Aswin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine and understand the liniage status of children resulting from fertilisasi in vitro process (test-tube baby) from surrogate mothers according to Islamic law and positive law. This research is included in the type of library research, which is a research carried out by collecting data from books and literatures from previous studies, using a normative juridical approach, and comparison. The research results found are as follows; First, the determination of the origin of the child in Islamic law is very important, because with that determination it can be seen the nasab relationship between the child and his parents. Second, the position of fertilisasi in vitro from the mother who replaces her lineage is cut off from her father because it is included in the act of adultery and only has the lineage of the one who gave birth to her. Third, the view of Islamic law on fertilisasi in vitro from a surrogate mother is unlawful, because its status is the same as adultery, resulting in mixed lineage and causing complicated problems. Meanwhile, according to positive law, fertilisasi in vitro from surrogate mothers is prohibited because it is not in accordance with article 127 of 2009 concerning health.